EKSKLUSI SOSIAL PENYANDANG DISABILITAS DI KOTA MAKASSAR - Ashar, Muhammad; K, Hairuddin (Social Landscape Journal, 2025)
People with disabilities are one of the social groups in society that often get bad treatment in society. The form of treatment they face, conceptually, is called social exclusion. Social exclusion contains various treatments such as stigmatization, discrimination, harassment and so on. People with disabilities should get protection as mandated by the law, but in reality social exclusion still occurs. This study aims to describe the process of social exclusion that occurs in Makassar City. The research method used is qualitative method. The findings of this study are that the process of social exclusion occurs through the scheme of Peter L Berger's Triadic Process in Social Construction Theory and the form of resistance to social exclusion is carried out through social counter-exclusion through structural and cultural strategies